The Impact of Interventions to Prevent Neonatal Healthcare-associated Infections in Low- and Middle-income Countries: A Systematic Review. Issue 3 (8th February 2022) - Fitzgerald, Felicity C.; Zingg, Walter; Chimhini, Gwendoline; Chimhuya, Simbarashe; Wittmann, Stefanie; Brotherton, Helen; Olaru, Ioana D.; Neal, Samuel R.; Russell, Neal; da Silva, André Ricardo Araujo; Sharland, Mike; Seale, Anna C.; et al.
Abstract : Background: Clinically suspected and laboratory-confirmed bloodstream infections are frequent causes of morbidity and mortality during neonatal care. The most effective infection prevention and control interventions for neonates in low- and middle-income countries (LMIC) are unknown. Aim: To identify effective interventions in the prevention of hospital-acquired bloodstream infections in LMIC neonatal units. Methods: Medline, PUBMED, the Cochrane Database of Systematic Reviews, EMBASE and PsychInfo (January 2003 to October 2020) were searched to identify studies reporting single or bundled interventions for prevention of bloodstream infections in LMIC neonatal units. Results: Our initial search identified 5206 articles; following application of filters, 27 publications met the inclusion and Integrated Quality Criteria for the Review of Multiple Study Designs assessment criteria and were summarized in the final analysis. No studies were carried out in low-income countries, only 1 in Sub-Saharan Africa and just 2 in multiple countries. Of the 18 single-intervention studies, most targeted skin (n = 4) and gastrointestinal mucosal integrity (n = 5). Whereas emollient therapy and lactoferrin achieved significant reductions in proven neonatal infection, glutamine and mixed probiotics showed no benefit. Chlorhexidine gluconate for cord care and kangaroo mother care reduced infection in individual single-center studies. Of the 9 studies evaluating bundles, most focused on prevention of device-associated infections and achieved significant reductions in catheter- and ventilator-associated infections. Conclusions: There is a limited evidence base for the effectiveness of infection prevention and control interventions in LMIC neonatal units; bundled interventions targeting device-associated infections were most effective. More multisite studies with robust study designs are needed to inform infection prevention and control intervention strategies in low-resource neonatal units.